A Cultural Anthropology of Head Porterage: Fresh Insights into Unique Markets - Akanle, Olayinka; Chioma, Chukwu (Himalayan Journal of Sociology and Anthropology, 2014)
In this article, we examined the repertoire of existences, processes and practises as well as mechanisms of open market place trading that is a definitive character of trading and associated dealings in many Sub-Saharan Africa countries which is as a result of the nature and structure of social and economic organizations cum cultural relational infrastructures of these Sub-Saharan societies. One stop shops and shopping malls that commonly punctuate American and European societies are rare necessitating special, unique and innovative ways of transporting goods and services across locations. It is within this socio-cultural, relational and economic infrastructural milieu that head porterage (Alabaru) subsists. Unfortunately, not many works exist in the areas of Anthropology and Cultural Studies on head porterage (Alabaru) which has assumed important character in the existences of most Sub-Saharan African markets with implications for global markets and world distribution/supply chains. This article therefore deployed robust Anthropological and qualitative methodology to examine the critical contours of the problematic. DOI: http://dx.doi.org/10.3126/hjsa.v6i0.10716 Himalayan Journal of Sociology and Anthropology Vol.6 2014: 166-186